INTRODUCTION OF LASER TECHNOLOGY CONTROLLED THERMO-CRACKING IN RUSSIA - V. S. Kondratenko; A. S. Naumov; A. Yu. Rogov (Российский технологический журнал)
The work is dedicated to the development of highly efficient technologies of precision cutting brittle non-metallic materials on the basis of a method of laser-managed thermosplitting (LCT), which gets recently the increasing distribution and worldwide recognition. Some examples of high-tech solutions to problems using the method of LCT on the Russian industrial plant MLP1-1060 / 355 for precise cutting of sapphire substrates and other brittle non-metallic materials. The paper analyzes the advantages of LCT method in comparison with common now cutting way - scribing laser picosecond. Visually-selling onstrate the practical results of such work as cutting instrument sapphire crystals on the plates; Sec-tion of sapphire substrates on elements critical to external influences; cutting instrument silicon wafers with OLED structures; narrow cutting sapphire substrates for LED lamps of the new generation; cutting circular tubes of different diameters and disc; cutting of tubes of square section and the square of elements of borosilicate glass; Development of technologies for creating grids on the surface of the optical elements. Cited in the results of the studies indicate that the successful use of the Russian LCT technology to solve problems of high-tech cutting plates of brittle non-metallic materials such as sapphire, glass, and silicon on the plant produced domestically.